Methodological and Statistical Concerns Regarding the Impact of Online Interactive Platform Services on Oral Health Behaviours in Older Adults With Mild Cognitive Impairment: Protocol for a Randomized Controlled Trial [Letter] - Rana E; Tah P (Journal of Multidisciplinary Healthcare)
Etika Rana, Priyanka Tah Maharishi Markandeshwar Institute of Physiotherapy and Rehabilitation, Ambala, Mullana, Haryana, IndiaCorrespondence: Priyanka Tah, Maharishi Markandeshwar Institute of Physiotherapy and Rehabilitation, Ambala, Mullana, Haryana, India, Tel +9734499769, Email priyankatah16@gmail.com